1997
DOI: 10.1007/s001340050297
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of infrared ear thermometry in adult patients

Abstract: Both rectal and esophageal thermistor measurements showed better agreement with pulmonary artery temperature than single ear themometry. Using the mean of two ear measurements improves the agreement and screening validity for detecting fever by rectal temperature. If temperature measurements are critical, esophageal measurements achieve excellent agreement with pulmonary artery temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
2
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 27 publications
4
53
2
3
Order By: Relevance
“…In a study 20 in 13 febrile patients, the oral thermometer was most accurately for detecting fever (>38.3°C), whereas the earbased measurement had the lowest chance of a false-negative reading. In 2 additional studies, 15,21 researchers evaluated the utility of ear-based temperature measurements for detecting fever (variably defined as a body temperature >38°C-38.5°C). In these studies, the ear-based thermometers also showed high specificity (0.92-1.00), indicating accuracy in identifying patients without a fever; but lower sensitivity (0.50-0.80) indicating accurate identification of only 50% to 80% of patients with a fever.…”
Section: Hyperthermia or Hypothermiamentioning
confidence: 99%
“…In a study 20 in 13 febrile patients, the oral thermometer was most accurately for detecting fever (>38.3°C), whereas the earbased measurement had the lowest chance of a false-negative reading. In 2 additional studies, 15,21 researchers evaluated the utility of ear-based temperature measurements for detecting fever (variably defined as a body temperature >38°C-38.5°C). In these studies, the ear-based thermometers also showed high specificity (0.92-1.00), indicating accuracy in identifying patients without a fever; but lower sensitivity (0.50-0.80) indicating accurate identification of only 50% to 80% of patients with a fever.…”
Section: Hyperthermia or Hypothermiamentioning
confidence: 99%
“…In recent years, several studies on the accuracy of IRT have been published with conflicting results. [14][15][16][17][18][19][20][21][22][23] We therefore evaluated the prototype in a population undergoing rapid changes in core temperature, using a large number FIGURE 1 Bland Altman plot of the paired measurements displayed against the average of the pair when the prototype of the infrared ear thermometer (IRT 4000) was compared to the pulmonary artery (PA) catheter.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, pulmonary artery thermometry was preferred as the reference method. [16][17][18][19][20][21][22][23] However, the statistical evaluation recommended by Bland and Altman 11 was not used in all studies. 16,17 This method considers that the result of any comparison of two instruments for clinical measurement can be due to technical errors in the reference method as well as in the new method to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…The rectum was selected as the site for body temperature measurement because of the difficulties and hazards associated with direct tympanic temperature measurement (1,15,16) associated with ear-based temperatures (1,(17)(18)(19)(20). Maternal rectal temperature was measured three times, just before anesthesia, at the beginning of operation and at delivery.…”
Section: Measurementsmentioning
confidence: 99%